Blastic plasmacytoid dendritic cell neoplasm (BPDCN): a rare entity. (20th January 2016) - Lim, Ming Sheng; Lemmert, Karla; Enjeti, Anoop
Abstract : Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive haematological malignancy in the elderly, with a high frequency of cutaneous and bone marrow involvement and poor prognosis. We report a case of BPDCN with classic presentation and discuss its treatment and the value of different investigation tools used in diagnosis and response assessment.